Decreased expression of Ras GTPase activating protein in human trophoblastic tumors. - Ståhle-Bäckdhal, M. (1995)
The normally developing placenta undergoes extensive but regulated noninvasive cellular proliferation. Various proto-oncogenes and growth factors have been associated with the regulation of trophoblastic placental growth. Activation of some oncogenes and altered expression of growth factors have been demonstrated in trophoblastic tumors (hydatidiform mole and choriocarcinoma). The ras proto-oncogene plays a key role in the signal transduction cascade of activated growth factors, and is known to be activated or overexpressed in multiple tumor types. Ras GTPase activating protein (RasGAP), a major down-regulator of ras activity, is present at high levels in placenta. To assess the role that Ras-GAP plays in the development of trophoblastic tumors, we performed immunohistochemical analyses with anti RasGAP antibodies of normal placentas, hydatidiform moles, invasive moles, and malignant choriocarcinomas. Normal placentas and noninvasive hydatidiform mole displayed intense positive staining confined to trophoblasts, whereas no staining was observed in the trophoblasts of invasive moles or choriocarcinomas. Thus, there was an inverse correlation between expression levels of RasGAP protein and the invasive potential and malignant phenotype in human trophoblastic tumors. The data indicate that RasGAP may play a regulatory role in trophoblast proliferation and that abolishing its activity may be associated with malignant transformation of these cells.